Efektivitas Donor Darah Bagi Kesehatan - Putri Utami; Abyena Hafza; Rizki Melinda Harahap; Usiono Usiono (Lembaga Pengembangan Kinerja Dosen, 2024)
Blood donation is the process of taking blood from someone voluntarily to be stored in a blood bank to be used for blood transfusions. This research aims to provide education to the public that blood donation has many benefits in the hope that there will be awareness of voluntary blood donation. The type of research carried out was descriptive qualitative research with data collection carried out by means of interviews, observation and documentation. The results of this research are that blood donation has a good effect on body health. Apart from that, the benefit of donating blood is that it helps reduce the risk of heart attacks and other heart problems and if blood donation is done regularly every three months, the body will produce new blood cells. The conclusion of this article is that blood donation has high effectiveness for health.